Comprehensive analysis of m6A circRNAs identified in colorectal cancer by MeRIP sequencing - He, Feng; Guo, Qin; Jiang, Guo-xiu; Zhou, Yan (Frontiers in Oncology, 2022)
Purpose: To characterize the entire profile of m6A modifications and differential expression patterns for circRNAs in colorectal cancer (CRC). Methods: First, High-throughput MeRIP-sequencing and RNA-sequencing was used to determine the difference in m6A methylome and expression of circRNA between CRC tissues and tumor-adjacent normal control (NC) tissues. Then, GO and KEGG analysis detected pathways involved in differentially methylated and differentially expressed circRNAs (DEGs). The correlations between m6A status and expression level were calculated using a Pearson correlation analysis. Next, the networks of circRNA-miRNA-mRNA were visualized using the Target Scan and miRanda software. Finally, We describe the relationship of distance between the m6A peak and internal ribosome entry site (IRES) and protein coding potential of circRNAs. Results: A total of 4340 m6A peaks corresponding to 2651 circRNAs were detected in CRC samples and 3216 m6A peaks corresponding to 2129 circRNAs were detected in NC samples. Pathway analysis detected that differentially methylated and expressed circRNAs were closely related to cancer. The conjoint analysis of MeRIP-seq and RNA-seq data discovered 30 circRNAs with differentially m6A methylated and synchronously differential expression. RT-PCR showned circRNAs (has_circ_0032821, has_circ_0019079, has_circ_0093688) were upregulated and circRNAs (hsa_circ_0026782, hsa_circ_0108457) were downregulated in CRC. In the ceRNA network, the 10 hyper-up circRNAs were shown to be associated with 19 miRNAs and regulate 16 mRNAs, 14 hypo-down circRNAs were associated with 30 miRNAs and regulated 27 mRNAs. There was no significant correlation between the level of m6A and the expression of circRNAs. The distance between the m6A peak and IRES was not significantly related to the protein coding potential of circRNAs. Conclusion: Our study found that there were significant differences in the m6A methylation patterns of circRNAs between CRC and NC tissues. M6A methylation may affect circRNA-miRNA-mRNA co-expression in CRC and further affect the regulation of cancer-related target genes.